2000
DOI: 10.1177/014556130007900711
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Septal Perforation: A Rare Extraintestinal Manifestation of Crohn's Disease

Abstract: Nasal manifestations of Crohn 's disease are quite rare. They are typified by chronic mucosal inflammation, obstruction, bleeding, and occasionally septalpelf orationsigns and sympto ms that are common to many disease states ofthe nose. Nasal finding s, much like oral lesions , can precede the more typical gastroenterologic manifestations of Crohn 's disease. Otolaryngologists should be aware ofsuch an association and consider the diagnosis of Crohn 's disease in atypical cases of nasal disease. We repo rt the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 14 publications
1
29
0
1
Order By: Relevance
“…In the literature, histologic findings of nasal CD were reported as chronic inflammatory changes similar to our case [3,8]. Authors demonstrated that in CD nasal histologic findings are similar to oral lesions where granulomas are detected in only 10-68% of specimens [11].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In the literature, histologic findings of nasal CD were reported as chronic inflammatory changes similar to our case [3,8]. Authors demonstrated that in CD nasal histologic findings are similar to oral lesions where granulomas are detected in only 10-68% of specimens [11].…”
Section: Discussionsupporting
confidence: 78%
“…2 Endoscopic nasal examination showed posterior nasal septal perforation approximately 2 cm in diameter mercaptopurine. He complained of nasal crusting, mild congestion, and epistaxis [3]. Our patient also had nasal septal perforation and severe gastrointestinal involvement requiring intensive immune suppressive therapy.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations